Use of Portable Infrared Cameras to Facilitate Detection and Capture Success of Montezuma Quail - Pedro M. Chavarria; Alison R. Kocek; Nova J. Silvy; Roel R. Lopez (National Quail Symposium Proceedings, 2017)
Survey and trapping methods for Montezuma quail (Cyrtonyx montezumae) require means not traditionally used for other quail species (e.g., northern bobwhite, Colinus virginianus). Trapping Montezuma quail is most effective using pointing dogs at night when coveys can be located and captured by net during roosting. However, reduced visibility at night, cryptic coloration of plumage, and behavioral adaptive stillness reduce detection rates and increase accidental flushing of birds while searching for roost locations. Forward-looking infrared (FLIR) cameras have been used to aid in detection of cryptic wildlife, including avifauna roosting sites. We conducted 25 survey and night-trapping sessions for Montezuma quail in southeast Arizona using a combination of trained pointing dogs and a portable FLIR camera. Detection of coveys on a roost was less successful when ambient climate conditions were freezing (below 3.88 8C), when residual heat signatures from surrounding soils and rocks were greater than 18.33 8C, or when density of grass cover exceeded 40% and the distance to covey was . 2.5 m. The small thermal signatures of quail were often obstructed by vegetative cover or confused with residual thermal signatures reflected by inanimate objects (e.g., rocks, bare ground). Successful detection of coveys combining the use of dogs and FLIR before trapping was 6.06%. Trapping success and detection of coveys with FLIR was improved when used with radiotelemetry and coveys which included radio-marked individuals. Proper tuning of FLIR camera sensitivity to a limited thermal bandwidth, or isotherm range, may effectively narrow covey locations approximated by a pointing dog. The FLIR camera was of limited benefit when actively trapping coveys with dogs and a team of 2–3 people, but may be beneficial for non-invasive monitoring and estimating covey size of marked birds on roosts in landscapes with reduced vegetative cover.
Keywords: Appleton-Whittell Research Ranch; Arizona; Coronado National Forest; Cyrtonyx montezumae; FLIR; forward-looking infrared; Mearn’s quail; Montezuma quail; roost; survey; trapping